Use of High Sensitivity Cardiac Troponin as An Early Diagnosis of Acute Myocardial Infarction (IMA): Systematic Review - Purwanti Nurfita Sari; Abu Bakar; Laily Hidayati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Acute myocardial infarction (IMA) is a leading cause of morbidity and mortality worldwide, so early diagnosis is needed to detect the disease. High sensitivity troponin assessment is a biomarker examination that can diagnose Acute Myocardial Infarction. The purpose of this study is to determine the effectiveness of the use of High Sensitivity Cardiac Troponin and as an early diagnosis of Acute Myocardial Infarction (IMA). This study is a systematic review study of 4 databases, namely Scopus, PubMed, EBSCO Host, and Sage Journals, with the keywords